A novel composite edible film based on quince seed gel and whey protein concentrate as affected by transglutaminase crosslinking - Gurbuz, Zeynep; Sengul, Mustafa; Erkaya-Kotan, Tuba; Saricaoglu, Furkan Turker (Wiley, 2024)
The development of edible films, which serve as a safe alternative to synthetic polymers by utilising by-products from the agricultural industry, has become a focus of research as they contribute to the sustainable use of resources. In the present study, quince seed gel (QSG) and whey protein concentrate (WPC) (1:1 w/w) were used as base components to develop edible films using glycerol as a plasticiser. The proteins were sonicated to denature and then the proteins were modified by cross-linking with the enzyme transglutaminase (TGase). The thickness, moisture content, solubility, permeability and digestibility of each edible films were investigated. In addition to the morphological, mechanical, optical, thermal and structural properties, the edible films were further characterised. The thickness, moisture, water vapour and oxygen permeability and the water solubility of the films were positively influenced by the cross-linking and the digestibility of proteins decreased with the cross-linking. A remarkable change in the secondary structures was observed in the FTIR spectra of the films. The stronger networks and their smooth surface of crosslinked films were confirmed by AFM images. The results of this research shows that QSG/WPC films cross-linked with TGase have potential for use in food packaging systems due to their advantages and may be an attractive alternative to synthetic materials in further studies. Innovative edible composite films were developed based on a new hydrocolloid-source gel from quince seed. Also, whey protein concentrate, an important by-product, was used as protein source. Transglutaminase (TGase) has been employed as a crosslinking agent. The mechanical, physico-chemical properties and thermal stability, surface structure and existing bonds were analysed. image
Keywords: Composite edible film; crosslinking; quince seed gel; transglutaminase; whey protein concentrate